The role of m6A modification during macrophage metabolic reprogramming in human diseases and animal models - Wang, Huiling; Xu, Peiqi; Yin, Kai; Wang, Shengjun (Frontiers in Immunology, 2025)
Macrophage metabolic reprogramming refers to the process by which macrophages adjust their physiological pathways to meet survival and functional demands in different immune microenvironments. This involves a range of metabolic pathways, including glycolysis, the tricarboxylic acid cycle, oxidative phosphorylation, fatty acid oxidation, and cholesterol transport. By modulating the expression and activity of key enzymes and molecules within these pathways, macrophages can make the transition between pro- and anti-inflammatory phenotypes, thereby linking metabolic reprogramming to inflammatory responses and the progression of several diseases, such as atherosclerosis, inflammatory bowel disease (IBD), and acute lung injury (ALI). N6-methyladenosine (m6A) modification has emerged as a critical regulatory mechanism during macrophage metabolic reprogramming, broadly affecting RNA stability, translation, and degradation. Therapeutic strategies targeting m6A modification can regulate the onset of metabolic diseases by influencing macrophage metabolic changes, for instance, small molecule inhibitors of methyltransferase-like 3 (METTL3) can affect glucose metabolism and inhibit IBD. This review systematically explores recent findings on the role and molecular mechanisms of m6A modification during macrophage metabolic reprogramming in human diseases and animal models, underscoring its potential as a therapeutic target for metabolic diseases.